2022
DOI: 10.3390/membranes12020231
|View full text |Cite
|
Sign up to set email alerts
|

Structures and Dynamics of Dengue Virus Nonstructural Membrane Proteins

Abstract: Dengue virus is an important human pathogen threating people, especially in tropical and sub-tropical regions. The viral genome has one open reading frame and encodes one polyprotein which can be processed into structural and nonstructural (NS) proteins. Four of the seven nonstructural proteins, NS2A, NS2B, NS4A and NS4B, are membrane proteins. Unlike NS3 or NS5, these proteins do not harbor any enzymatic activities, but they play important roles in viral replication through interactions with viral or host pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 160 publications
(249 reference statements)
0
9
0
Order By: Relevance
“…Recently, several repurposed drugs were evaluated against dengue virus, including sinefungin, ivermectin, lovastatin, prednisolone, modipafant, ketotifen, balapiravir, ribavirin, celgosivir, UV-4B, and chloroquine, but no signicant success has been reported yet. 23 Saturation transfer difference (STD-NMR) is a robust technique for the analysis of protein-ligand interactions, as well as for the identication of binding epitopes of a ligand. In this study, 75 compounds were evaluated against NS5 from our inhouse library, including US-FDA approved drugs and natural products, using saturation transfer difference (STD)-NMR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several repurposed drugs were evaluated against dengue virus, including sinefungin, ivermectin, lovastatin, prednisolone, modipafant, ketotifen, balapiravir, ribavirin, celgosivir, UV-4B, and chloroquine, but no signicant success has been reported yet. 23 Saturation transfer difference (STD-NMR) is a robust technique for the analysis of protein-ligand interactions, as well as for the identication of binding epitopes of a ligand. In this study, 75 compounds were evaluated against NS5 from our inhouse library, including US-FDA approved drugs and natural products, using saturation transfer difference (STD)-NMR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several repurposed drugs were evaluated against dengue virus, including sinefungin, ivermectin, lovastatin, prednisolone, modipafant, ketotifen, balapiravir, ribavirin, celgosivir, UV-4B, and chloroquine, but no significant success has been reported yet. 23 …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the thumb domain has an initiation loop, which is primarily responsible for facilitating the initiation of ATP-specific RNAs and regulating the transition of subsequent elongation steps ( Bartholomeusz and Thompson, 1999 ). The finger domain is involved in the formation of the active site and NTP entry channel by controlling the de novo synthesis of RdRp ( Akiyama et al, 2021 ; Li and Kang, 2022 ). Finally, alanine substitutions have demonstrated that several N-pocket residues are critical for NS5 polymerase de novo activity as well as viral replication ( Ackermann and Padmanabhan, 2001 ; Malet et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…The genome contains one open reading frame and encodes a polyprotein that can be further processed into 10 proteins by both host and viral proteases. These viral proteins include three structural proteins namely capsid protein (C), premembrane protein (prM) and envelope protein (E) and seven nonstructural proteins (NS1, NS2A, NS2B, NS3, NS4A, NS4B and NS5) ( Pierson and Kielian, 2013 ; Li and Kang, 2022 ). The structural proteins are the key components of viral particles.…”
Section: Introductionmentioning
confidence: 99%